The Brazilian Practices for Handling Sustainability in Software Engineering: a Replicated Survey - Melo, Rodrigo; Vilela, Jéssyka; Silva, Carla; Peixoto, Mariana; Araújo, João (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
Context: The demand for all economic activities to adopt sustainable practices, including software development, is increasing. Addressing sustainability in software development can lead to improvements in the products and services offered and significantly contribute to the quality of life of the entire society. Objective: This study aims to understand the level of knowledge and practices adopted by Brazilian software developers regarding sustainability in their work. Method: we conducted a replicated survey that received responses from 21 individuals working in organizations dedicated to software development. Results: we identified the impact of sustainability on their working environment, including which methods and tools are used in Brazilian software development companies. Conclusions: Brazilian developers showed greater concern with sustainability in their work. However, they still face considerable challenges, such as a lack of specialists in the field and the dissemination of this knowledge among development teams.